Design of metallic nanostructures for plasmonics based applications : chemo/biosensing, solar evaporation, and photocatalysis - Zhang, Lulu (2018)
Metallic nanostructures based plasmonics have been widely studied and proven as powerful platforms in biosensing, photocatalysis, surface enhanced Raman spectroscopy (SERS) and solar energy harvesting related studies. The broad application potentials of plasmonics make people find more and more interesting phenomena and propose even more novel and useful applications based on this fascinating technology. The phenomena of analytes induced shift of surface plasmon resonance (SPR) of gold nanoparticles (Au NPs) and the color changes of Au NP solutions offers a simple and effective strategy of constructing colorimetric sensing systems. However, most of the Au NPs colorimetric sensing systems developed in previous studies were designed and aiming at the sensing/detection of one certain target/analyte, and unable to be employed for multiple analytes sensing/discrimination. In this thesis, by introducing the concept of logic gate in constructing plasmonic colorimetric sensing system and taking advantage of the highly specific competing coordination reactions between the targeted analytes, we designed for the first time an integrated Au NPs colorimetric sensing platform which can achieve the sensing of Hg2+, melamine, and cysteine. In the field of plasmonics, application-based studies were mostly relying on the limited candidate metals such as Au and Ag which are noble metals, which hampers the design of novel LSPR based systems to be employed in a broad range of practical applications. In this thesis, we have designed different plasmonic nanostructures by using indium which is a kind of poor metal for different applications: (1) Taking advantage of the superior plasmonic heating ability of In NPs and the simple device fabrication process when compared to other metals/materials, we prepared In NPs on a paper like microporous membrane (MPM) to achieve a portable device with broad light absorbing ability, which showed enhanced solar evaporation performance. As a proof of concept, its application was demonstrated in the solar desalination of the real seawater sample with high stability; (2) In NPs with UV and Visible LSPRs prepared on quartz substrates were coated with layer of TiO2 NPs, the substrate showed an enhanced photocatalysis performance for the degradation of methylene blue when compared with substrate which only had TiO2 coating. The UV and Visible LSPRs can benefit the enhancement through both the hot carrier injection and near-field enhancement mechanisms, while for previous studies using Au, Ag, and Al, only one of the two mechanisms can be observed; (3) In NPs were prepared on ITO with 300 to 400 nm LSPR can be used for UV SERS using 325 and 355 nm laser, which can achieve comparable enhancement when compared to Al, and better enhancement when compared to previous study using In NPs with 266 nm excitation. Our strategy on the Au NPs colorimetric logic gate may be extended to the design of logic gate sensing systems by using other techniques such as SERS and fluorescent sensing, or other analytes with specific coordination interactions. Our findings in In NPs based systems can help others gain further insight of the plasmonic properties of In NPs, which may on other hand inspire the design of other novel applications and broaden their capabilities in different fields. In the future, I will try to improve the synthesis of In NPs to obtain In NPs with good size and shape control. Then we can have an in-depth fundamental study of the size and shape induced LSPR property of In NPs, such as single particle UV plasmonics of In NPs both theoretically and experimentally. I will also try to design other novel applications based on the superior plasmonic heating ability of In NPs and its UV LSPR feature, for example, to combine the plasmonic heating effect of In NPs with the photocatalysis of TiO2 together, to achieve simultaneously water treatment and evaporation.